Planeación óptima de redes de distribución eléctrica aérea usando métodos heurísticos y procesos de simulación. - Herrera Cisneros, Esteban Bladimir (2018)
This article is intended a planning model for the deployment of the overhead electrical distribution systems, which allows under heuristics and optimization criteria to reduce the cost of resources associated in the construction of the network; it shows an optimal deployment of distribution transformers considering technical restriction and capacity. The model presents warm a routing on a geo-referenced scenery with information from the OpenStreetMap platform, with the purpose that the topology of the net is under real condition and design of a city; furthermore, the minimum Steiner tree is used for the overhead distribution network. Additionally, the model attaches of scalability and flexibility principles, adjusting the results to variations in different scenarios. On the other hand, with Cymdist software simulation verified the electrical parameters to involved in the design of overhead network. Results obtained present for electrification companies a reference points for future planning of the electricity distribution networks, adapting to the random changes in demand.